‘It is the Journey not the Finish Line’: Predictors of Grit in the Way of St. James Pilgrimage - Nunes, Ana Rita (The international journal of religious tourism and pilgrimage, 2023)
Few studies have explored how individuals can develop perseverance and passion towards longterm goals. This study addresses this research topic. Predictors of grit were tested while participants progressed on the Way of St. James, a long walk completed by foot or bicycle, taking several days or weeks, to Santiago de Compostela (Spain). 575 pilgrims of various nationalities self-reported measures of grit, harmonious passion, autonomous functioning, and lifelong learning attitudes. To study the association between these variables, path analysis modelling was conducted. The results show that autonomous pilgrims demonstrate more perseverance and passion towards their long-term goals than less autonomous pilgrims. Moreover, pilgrims who reported positive lifelong learning attitudes showed more grit behaviours than their counterparts with fewer lifelong learning attitudes. Finally, results indicate a strong association between autonomy and lifelong learning attitudes. The main conclusions suggest that perseverance with passion towards a long-term goal increases when individuals are congruent with their own interests and values, are not very susceptible to external or internal pressures, and are open to continuing to improve their knowledge and skills, regardless of age. Some implications for future research and practice are also addressed in this paper.